Prevention guide for designers based on analysis of about 2000 accidents - Alfredo Soeiro (2014)
Accident prevention in the design stage of the project is characterized by proactive and effective actions, and analyzing the risks of accidents at the beginning of the life cycle of the project can ensure that safety measures at the stage of implementation, of maintenance and of deconstruction are already in place. This thesis aims to contribute to filling this gap by presenting a proposal for a management model of the prevention of risks of accidents at work at the design phase. This model was obtained by analyzing accidents at work occurring in the construction sector in order to identify links between the causes of accidents and the designs. In order to do this analysis the MAARD-Method of Analysis for Accident Related Design was created and applied. The method results in an analysis in which a conclusive answer can be obtained about the existing link between the causes of the accident and the different types of designs in order to determine which could be involved. The preventive measures to be implemented in design phase were also determined. Based on the analyses of accidents a framework for designers was created. The framework originated a model called MMPtD - Management Model for Prevention through Design. This model consists mainly of a guide that may help designers decide measures to prevent risks during construction. Another conclusion from the study was that an average of 60.8% of the accidents could have been prevented during the stages before construction. Excluding the planning phase from this analysis an average of 35.1% of accidents could have been prevented with measures during the conceptual design. Of these designs architecture and structure designs were singled out as projects of greater impact in the prevention of accidents.